Computer aided diagnosis of diabetic foot using infrared thermography: A review. (1st December 2017) - Adam, Muhammad; Ng, Eddie Y.K.; Tan, Jen Hong; Heng, Marabelle L.; Tong, Jasper W.K.; Acharya, U. Rajendra
Abstract: Diabetes mellitus (DM) is a chronic metabolic disorder that requires regular medical care to prevent severe complications. The elevated blood glucose level affects the eyes, blood vessels, nerves, heart, and kidneys after the onset. The affected blood vessels (usually due to atherosclerosis) may lead to insufficient blood circulation particularly in the lower extremities and nerve damage (neuropathy), which can result in serious foot complications. Hence, an early detection and treatment can prevent foot complications such as ulcerations and amputations. Clinicians often assess the diabetic foot for sensory deficits with clinical tools, and the resulting foot severity is often manually evaluated. The infrared thermography is a fast, nonintrusive and non-contact method which allows the visualization of foot plantar temperature distribution. Several studies have proposed infrared thermography-based computer aided diagnosis (CAD) methods for diabetic foot. Among them, the asymmetric temperature analysis method is more superior, as it is easy to implement, and yielded satisfactory results in most of the studies. In this paper, the diabetic foot, its pathophysiology, conventional assessments methods, infrared thermography and the different infrared thermography-based CAD analysis methods are reviewed. Graphical abstract: Highlights: Pathogenesis and burden of diabetic foot is reviewed. Automated diagnosis methods of diabetic foot are studied. Various infrared thermography methods are discussed. Asymmetric temperature analysis has yielded better results.